Symbolic approximation for computer vision - Blake, Richard E. (Nonlinear Analysis: Modelling and Control, 1998)
The need for a definition of discrete convergence in matching problems, which are essential in computer vision, is described and the fundamental properties of Scott lattice theory are outlined. Three data types: relational graphs, graph match_table and constraints, are considered and partial orderings are exhibited for them. A matching iteration consistent with the theory is sketched.
Keywords: none